PENGARUH KUALITAS PRODUK DAN NILAI NASABAH TERHADAP KEPUASAN DAN LOYALITAS NASABAH KREDIT PADA PD. BPR BANK DAERAH SUKOHARJO - BRM. Suryo Triono; Adi Penawan; Aris Tri Haryanto (STIE AUB Surakarta, 2020)
ABSTRACTThe purpose of this study is to know, analyze and prove empirically the influence of product quality and customer value to customer satisfaction and loyalty credit at PD. BPR of Bank Daerah Sukoharjo. Analytical technique used is by using instrument test which includes test of validity and reliability test, linearity test, regression analysis, path analysis, t test, F test, coefficient determination test and correlation analysis. The t test results show: Product quality has positive and significant effect to satisfaction and proven to be true. The value of the customer has a positive and significant impact on satisfaction and proven true. Product quality positively and positively affects loyalty and is proven true. The value of the customer has a positive and significant impact on loyalty and is proven true. Satisfaction has a positive and significant effect on loyalty and proven to be true. F test results can be concluded together product quality variables, customer value and satisfaction have a significant effect on loyalty. The result of calculation of total R2 value of 0.707 can be interpreted variations of loyalty of credit customers in PD. The BPR of Bank Daerah Sukoharjo is explained by the variable of product quality, customer value and satisfaction of 70.7%. The conclusion of path analysis is as follows: Direct influence Product quality to loyalty of 0.372, while indirect influence of 0.078 so as to increase loyalty more effectively through direct line. Direct influence Customer value to loyalty of 0.267, while the indirect effect of 0.037 so as to increase loyalty more effectively through direct line. Keywords: Product Quality, Customer Value, Satisfaction, Customer Loyalty